An empirical study of Educational Mobility Management to Develop a Short Term Program: A Case Study of TDM promotion plan in Hadano City - HIRAISHI, Hiroyuki; FUJII, Satoshi; TANIGUCHI, Ayako (INFRASTRUCTURE PLANNING REVIEW, 2006)
To implement Educational Mobility Management (MM), school organization for the acceptance of the lecture and which subject is well suited to MM are recognized as the important issue. One of the way to solve these problems is to develop the program being able to implement easy and short duration. In this study, we implemented an Educational MM program in Hadano city, and measured the effectiveness for the children before and after the program, and ten months after the program by questionnaire survey, and collected advice to improve the program by interview survey for the teachers. We analyzed the data measured by questionnaire, the data suggested that the effectiveness of the program was continued after the ten months of the lecture.